Cloning and expression of Voltage-dependent Anion Channel 2 (VDAC2) from electrically stimulated chicken - Ahmad Hassan, Nurhidayah; Amid, Azura; Mohd. Salleh, Hamzah (Journal of Pure and Applied Microbiology, 2013)
VDAC2 protein identified to be overexpressed in stunned chicken is a potential biomarker in differentiating stunned chicken since the expression was proportional to the voltage applied. To facilitate research, the gene encoding VDAC is cloned, expressed and optimized in BL21-AI Escherichia coli. cDNA was synthesized from mRNA of stunned chicken’s skeletal muscle and cloned using recombination reaction. All positive clones were identified by PCR and restriction enzyme digestion as well as DNA sequencing. Recombinant VDAC2 protein was purified by Ni-NTA spin-column. Western blot performed using polyclonal anti-N terminal human VDAC2 and anti-His tag revealed a 34 kDa protein, confirming the expression of recombinant VDAC2.